PENGARUH MOTIVASI BERORGANISASI DAN KOHESIVITAS KELOMPOK TERHADAP KOMITMEN BERORGANISASI (STUDI MAHASISWA AKTIVIS FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG) - Maulina Syafitri; Armida S (Universitas Negeri Padang, 2019)
Abstract : This research was conducted to determine the effect of organizational motivation and group cohesiveness on organizational commitment of activists of the Faculty of Economics, State University of Padang. This type of research is quantitative descriptive. The population in this study was activist students of the Faculty of Economics, Padang State University in 2019 with a population of 885 and a sample of 90 people. Sampling was determined using the Slovin formula with Proportional random sampling technique. Data collection techniques used in this study were questionnaires. The validity test uses SPSS version 23 seen in the Corrected Item-Total Correlation column and the reliability test seen in the Cronbach Alpha column. Analysis technique used is multiple linear regression. To test the hypothesis the F test and t test were used, using the SPSS version 23 program. The results of this study indicate that (1) organizational motivation and group cohesiveness have a positive and significant influence on the organizational commitment of activists at the Faculty of Economics, Padang State University. (2) Organizational motivation has a positive and significant influence on the organizational commitment of activists in the Faculty of Economics of Padang State University, (3) Group cohesiveness has a positive and significant effect on the organizational commitment of activists of the Faculty of Economics, Padang State University. Keywords: organizational motivation, group cohesiveness, organizational commitment